Sizing for battery powered, non-rigid, finless airship for low altitude application - Mohd Harithuddin, Ahmad Salahuddin; Sedan, Mohd Fazri; Gires, Ezanee (Aeronautical and Astronautical Society of the Republic of China, Taiwan, 2024)
A smaller airship with sub-100 kg payload capacity offers practical advantages, such as ease of operation, versatility, and reduced helium consumption. Payload weight significantly influences hull sizing and correlates with airship flight subsystems like power and propulsion. This paper presents a method for determining the dimensions of a basic lighter-than-air vehicle, consisting mainly of a non-rigid envelope hull, tiltable electric rotors, and a gondola housing the flight subsystems. The airship is designed to emulate a low-altitude multirotor drone but with enhanced buoyancy-based lifting capacity and flight endurance. Flight endurance, speed, and hull shape (fineness ratio) are held constant, using a prebuilt airship as the baseline design for performance measurement. Surveys of electronic components aid in estimating airship subsystem weights. The sizing method indicates that a four-rotor, finless, non-rigid airship with a 100 kg payload and over 25.5 kg battery capacity, capable of 2 hours of flight, requires 220 m³ of helium. With a fineness ratio of 2.03, the airship hull spans under 15 m. This sizing tool and analysis facilitate scalable design, aiding airship builders in transitioning from small experimental models to practical low-altitude applications.